Anomalodesmata - Prezant, Robert (Mollusca: The Southern Synthesis, Part A, Fauna of Australia Volume 5, 1998)
Keywords: dept.aa

Heterodonta, Introduction - Prezant, Robert (Mollusca: The Southern Synthesis, Part A, Fauna of Australia Volume 5, 1998)
Keywords: dept.aa

Palaeoheterodonta, Introduction - Prezant, Robert (Mollusca: The Southern Synthesis, Part A, Fauna of Australia Volume 5, 1998)
Keywords: dept.aa

Class Bivalvia - Prezant, Robert; Morton, B; Wilson, B (Mollusca: The Southern Synthesis, Part A, Fauna of Australia Volume 5, 1998)
Keywords: dept.aa

Effects of Stream Chemistry on the Distribution, Growth, and Diatom Colonization of the Freshwater Limpet, Ferrissia rivularis - Keating, S. T.; Prezant, R. S. (Journal of Freshwater Ecology, 1998)
The freshwater limpet, Ferrisla rivularis, was found in several watersheds in south-central and south-western Pennsylvania. Shell size was not significantly correlated with stream pH, calcium, iron, or manganese concentrations. Limpets tolerated stream iron concentrations up to 0.36 mg/l and manganese concentrations up to 0.25 mg/l. The shells of these snails were quickly and heavily colonized by adherent or embedded diatoms, and shell size was significantly positively correlated with diatom coverage (P=0.050). Diatom coverage was significantly positively correlated with stream phosphate concentration (P=0.002).
Keywords: dept.aa